Exploring the Links Between Receiving Special Education Services and Adulthood Outcomes - Kanaya, Tomoe; Wai, Jonathan; Miranda, Brenda (Frontiers in Education, 2019)
A majority of the research on students receiving special education services have focused on school-aged outcomes, such as academic performance. Comparatively less is known about how these students fare in adulthood. By utilizing a one-to-one propensity score matching technique, individuals who received special education services were compared with those who did not on multiple adulthood outcomes that span educational attainment, economic self-sufficiency, social engagement and health. Results suggest that Hispanic students in our sample who participate in special education fared better compared to their White counterparts on some outcomes. Moreover, the contextual factors that increase the likelihood of receiving services (e.g., maternal education) predicted several more outcomes. These results point to the potential importance of the contextual factors that surround special education, suggest the need to provide context-specific services at the local level, and highlight the use of propensity score analyses to reduce concerns of selection bias in educational research.